2003
DOI: 10.1046/j.1471-5740.2003.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Use limitations of alcoholic instant hand sanitizer as part of a food service hand hygiene program

Abstract: The efficiency of either handwashing or use of alcoholic instant hand sanitizers (AIHS) has been reported against normal microflora (NF) or transient microflora (TF) using marker bacteria or viruses. Most studies were performed to support use in health care employing techniques that poorly mimic food service. When AIHS is used alone, application quantity, exposure period, alcoholic concentrations and type influence effectiveness. Relevant to the food industry, little work has been done in order to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
0
21
0
1
Order By: Relevance
“…Michaels et al . (2003) reported that the combination of hand washing followed by alcohol‐based sanitizer lotion significantly reduced bacterial numbers compared to hand washing alone only when large quantities (3 and 6 mL) of sanitizer were applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Michaels et al . (2003) reported that the combination of hand washing followed by alcohol‐based sanitizer lotion significantly reduced bacterial numbers compared to hand washing alone only when large quantities (3 and 6 mL) of sanitizer were applied.…”
Section: Resultsmentioning
confidence: 99%
“…Factors affecting alcohol‐based sanitizer effectiveness include alcohol type, alcohol concentration, quantity applied, exposure time and organic load on hands (Kramer et al . 2002; Michaels et al . 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cultures have a strong tradition of washing hands before eating, but often with cold water and without soap (Hoque, 2003;Hoque & Briend, 1991). Although washing of hands with water alone reduces microbial loads on hands (De Wit & Kampelmacher, 1981;Michaels, 2002;Michaels, Ganger, Chia-Min, & Doyle, 2003), a combination of sanitizers and/or detergents and warm water have demonstrated to be more effective (Cogan, Bloomfield, & Humphrey, 1999;Courtenay et al, 2005;Josephson, Rubino, & Pepper, 1997;Michaels et al, 2003). In Bangladesh, during post-defecation hand washing, women living in the semi-urban rub their hands with soil, soap or ash and rinse them with safer water (tube well water) followed by drying with a clean cloth.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers who recommend hand sanitizers over soap-water hand washing have pointed out that soap-water hand washing fails to remove biotic or living organisms, and the possibility exists for soap contamination (Cardoso, Pereiraa, Zequimb, & Guilhermettia, 1999). Other researchers have concluded that soap-water hand washing is less efficient than hand sanitizers (Johnson, et al, 2005;Michaels, Gangar, lin, & Doyle, 2003;Widmer, 2000). In 2002, the CDC revised their…”
Section: Hand Sanitizer History and Efficacymentioning
confidence: 99%